(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researcher conducted this study to evaluate the psychological pressure on changes in food preference among Gen Z psychology students. The result showed the ages of twenty-one (21) to twenty-three (23) represent the highest frequency of the respondent in total, at 45%. CIS-GENDER comprises the majority of the sample, with 78 respondents, while LGBTQAT comprises twenty-two (22) respondents. The composite mean result of stress (2.43), depression (2.05), and the highest composite mean result of anxiety (2.77) revealed that the majority of respondents believe that food can reduce anxiety. Next, the composite mean result for families (2.88) shows that respondents prefer homemade food. Meanwhile, friends (2.60) show that the respondent loves to eat fast food with friends. According to the study, there is currently psychological pressure on psychology students to alter their eating preferences. It is advised that individuals be more conscious of their food preferences and observant of their emotions. Their acquaintances ought to show consideration as well.